Circulating SFRP5 levels are elevated in drug‐naïve recently diagnosed type 2 diabetic patients as compared with prediabetic subjects and controls. Issue 2 (21st October 2014) - Canivell, Silvia; Rebuffat, Sandra; G. Ruano, Elena; Kostov, Belchin; Sisó‐Almirall, Antoni; Novials, Anna; Ceriello, Antonio; Gomis, Ramon
Abstract Background Secreted frizzled‐related protein 5 (SFRP5) has been linked to obesity. Results are conflicting regarding its association with type 2 diabetes (T2D) in humans. We aimed to investigate circulating SFRP5 in prediabetes and T2D and its potential association with parameters of insulin resistance and beta‐cell function. Methods We studied 70 drug‐naïve T2D patients, 70 prediabetic subjects and 70 controls. All subjects were body mass index matched to the T2D patients and overweight or obese. SFRP5, hormones and cytokines levels were measured by ELISA. Results Serum SFRP5 levels were elevated in T2D patients as compared with prediabetic subjects (median 15.6, interquartile range [9–24.5] ng/mL vs 9.8 [5–14.2] ng/mL, p < 0.001, respectively) and controls (15.6 [9–24.5] ng/mL vs 10.4 [6.7‐16.6] ng/mL, P < 0.001, respectively). No differences were found in serum SFRP5 levels between prediabetic subjects and controls (9.8 [5–14.2] ng/mL vs 10.4 [6.7–16.6] ng/mL, p = 0.472, respectively). After adjusting for potential confounders (age, gender, body mass index, triglycerides, high‐density lipoprotein cholesterol and blood pressure), T2D was still associated with higher values of SFRP5 as compared with prediabetes in multinomial logistic regression analysis (fully adjusted odds ratio 3.50, 95% confidence interval 1.40–8.79, p = 0.008). The association was more subtle when comparing T2D with normal glucose tolerance state (fully adjusted odds ratio 2.18, 95% confidence interval 0.91–5.21, p = 0.078). Conclusions Circulating SFRP5 levels were independently associated with T2D as compared with prediabetes and normal glucose tolerance state. Copyright © 2014 John Wiley & Sons, Ltd.